Political Identity, Popular Culture, and Ideological Coercion: The Discourses of Feminist Movement in the Report of Ummi Magazine - Diah Handayani (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
This research examines the rise of Islamic populism in Indonesia and understands it as an instrument to clear a new pathway for populism movement into popular culture. Ummi magazine is one of the religious media used to be political vehicles of stablishing constituencies, especially for the Tarbiyah movement in the Soeharto era to the current tendency to popularize the Tarbiyah identity as a new lifestyle. Historically, The Tarbiyah movement in Indonesia is a social and political movement among Indonesian Muslimah students, especially activists in the Suharto period. Muslim middle class entrepreneurs launched a campaign of ‘economic jihad. This research uses a qualitative approach by interpreting and studying the data contained in Ummi Magazine. Media studies were carried out in the January 2017 to 2018 editions. The data obtained were described and associated with the magazine's transformation as an ideological medium and Muslim women's lifestyle today. The result shows that the magazine's transformation from ideology magazine to lifestyle magazine can influence readers because there are more new readers. Whether Ummi as a media for da'wah and a women's magazine, it is still perceived by the readers to apply ideological coercion or simply provide an alternative lifestyle or consumption where religious independence is the main characteristic of the magazine. We argue that Islamic populism is mainly a medium for coercion ideology to gain tracks to power, while the poor remain as ‘floating mass’, and entrapped in many so-called 'empowerment' projects. Populism can be interpreted as a communication style in which a group of politicians considers themselves to represent the people’s interests contrasted with elite interests. Nevertheless, the populism approach is gaining momentum.